Advanced Therapies in Venous Thromboembolism. Issue 3 (July 2017) - Yadam, Suman; Sharara, Rihab; Naddour, Mouhib; Beg, Moeezullah; Singh, Anil C.; Balaan, Marvin
Abstract : Advanced therapies are available for both deep venous thrombosis and pulmonary embolism when anticoagulation alone is not sufficient to improve clinical outcomes. In some cases, clinical deterioration ensues despite anticoagulation, and this requires unique techniques that can ameliorate the clinical course. Such advancements are described in this upcoming article.